Peran Teresa Magbanua dalam Revolusi Filipina 1898 - Prameswari, Dita Putri (Indonesian Character Journal, 2024)
This paper will discuss the role of Teresa Magbanua during the Philippine Revolution against Spain in the provinces of Capiz and Iloilo in the Western Visayas region from November to December 1898. Teresa Magbanua, who had a background as a schoolteacher in Iloilo, obtained her teaching certificate from Colegio de Dona Cecilia and completed her postgraduate education at the University of Santo Tomas in Manila. Magbanua led Filipino troops under the Katipunan organization, which was established in 1892 with the aim of opposing Spanish colonial rule. During the conflict with Spanish forces, Magbanua and her troops employed guerrilla warfare strategies. Her struggle concluded in December 1898 with the signing of the Treaty of Paris between Spain and the United States. Furthermore, this paper will explore Magbanua's role in organizing military strategies and combat tactics during the Philippine Revolution. Following the end of the war, Philippine revolutionary leader Emilio Aguinaldo declared independence, marking the end of Spanish rule and the beginning of Philippine independence. This study will employ historical methods consisting of four stages: heuristics, criticism, interpretation, and historiography, utilizing both primary sources such as archives and secondary sources such as books, journals, and dissertations. The findings of this research will highlight the impact of Teresa Magbanua's role after the Philippine Revolution and identify best practices that can be learned from her contributions to the revolution. Keywords: Teresa Magbanua; Philippine Revolution; colonialism Â  Makalah ini akan membahas peran Teresa Magbanua di masa Revolusi Filipina ketika menghadapi Spanyol di Provinsi Capiz dan Iloilo di wilayah Visayas Barat pada November hingga Desember 1898. Teresa memiliki latar belakang sebagai guru sekolah di Iloilo. Ia meraih sertifikat guru di Colegio de Dona Cecilia dan berhasil menyelesaikan pendidikan pascasarjana di Universitas Santo Tomas, Manila. Teresa Magbanua memimpin pasukan tentara Filipina yang berada di bawah organisasi Katipunan. Katipunan adalah organisasi yang dibentuk pada 1892 yang bertujuan melawan kekuasaan kolonialisme Spanyol. Selama bertempur melawan kekuasaan Spanyol, Teresa Magbanua bersama pasukannya menggunakan strategi perang gerilya. Perjuangan Magbanua berakhir pada Desember 1898 dengan ditandatanganinya Perjanjian Paris antara Spanyol dengan Amerika Serikat. Lebih jauh, tulisan ini akan mengeksplorasi peran Magbanua dalam mengatur strategi perang dan taktik pertempuran di masa revolusi Filipina. Dengan berakhirnya perang, pemimpin revolusi Filipina yaitu Emilio Aguinaldo mendeklarasikan kemerdekaan yang menandai kemerdekaan Filipina dan berakhirnya kekuasaan Spanyol. Penelitian ini akan menggunakan metode sejarah yang terdiri dari empat tahapan yaitu heuristik, kritik, interpretasi dan historiografi, serta menggunakan baik sumber primer seperti arsip maupun sumber-sumber sekunder berupa literatur dalam bentuk buku, jurnal, dan disertasi. Hasil dari penelitian ini adalah munculnya dampak dari peran Teresa Magbanua setelah Revolusi Filipina berlangsung dan adanya praktik baik yang dapat dipelajari dari peran Teresa Magbanua dalam revolusi.